On the Eve of 'Vanmahotsava', 1982 - Oza, G. M. (Indian Forester, 1983)
The urbanisation plans in many of our Indian cities seem to be Cruel to plant life. We axe down plant species and put an end to nation's excellent, valuable, cultural asset. Thus, we may head for a future in which indigeuous floristic elements in India and the heritage of the past civilization will face survival problems. Moreover, during 'Vanmahotsava' celebrations, we introduce 'allergic' ornamental trees which contribute to our miseries. The author pleads to endeavour to nourish only the 'natural flora'-the representative elements of the forest trees in each of our States and trees know in historical literature, but in no case we should go in for foreign importations, irrespective of their beautifulness or the source of timber. We can establish for future generation a 'living museum of trees typical to our country'. Some of the data pertaining to endangered Indian flora bave been presented.